Moons and planets - Hartmann, William K. (Belmont, Wadsworth Publishing Company, 1999)
This text is organized by physical topic (planetary surfaces, planetary interiors, atmosphere, and so on), which allows for comparative planetology. To show the subject as a science, rather than a group of facts, Hartmann develops general principles and applies them to various planets, demonstrating unifying processes that cause similarities and differences among worlds, from ring structure to craters to atmospheric greenhouse effects.
Appendix 392-395p; Bibliographical references 397-418p; Index 419-428p
Keywords: Physics; Solar System; Planetology